Autotransmogrification in Asaf Hanuka's 'The Realist' as critique on Israeli society. Issue 3 (4th May 2021) - Reingold, Matt
ABSTRACT: One of the artistic techniques that Asaf Hanuka employs in his weekly autobiographical comic strip 'The Realist' is distorting his own face. Through this transformation, Hanuka provides a critique of Israeli society and the ways that ethnic and religious identities are constructed in the country. Terming this technique autotransmogrification, I consider four specific comics where in each Hanuka changes his face nine different times. In these comics Hanuka directly addresses his own identity as an Israeli Jew whose ethnicity is Arab, and through these transformations, he addresses the ways that racism and exclusionary policies have left him feeling marginalised within his country. Through the creative process of autotransmogrification, Hanuka is able to challenge the constructs of racial and ethnic identity within the country, and by radically envisioning himself in new ways, provide non-hegemonic models for understanding what it can mean to be Israeli.